2013
DOI: 10.3354/dao02546
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive and specific LAMP PCR assay for detection of fish pathogen Lactococcus garvieae

Abstract: Based on use of a loop-mediated isothermal amplification (LAMP) identification protocol, this study attempted to detect Lactococcus garvieae in fish by using primer sets designed from an L. garvieae alpha/beta fold family hydrolase gene. Reaction time and temperatures were optimized for 60 min at 60°C with the resulting amplicons visualized by adding SYBR Green I to the reaction tube. The assay specificity was assessed using 45 different bacterial strains. Positive results were observed in all 30 L. garvieae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…3), indicating that the LAMP method can detect the presence of target DNA in a crude extract of DNA solution obtained by the toothpick method. Although we tested PCR only with one primer set and one taq PCR kit, similar sensitivity as LAMP was not observed for the PCR method, thus corroborating previous reports that the LAMP method is superior to the PCR method in sensitivity (Kikuchi et al 2009;Nakao et al 2010;Thekisoe et al 2005;Tsai et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…3), indicating that the LAMP method can detect the presence of target DNA in a crude extract of DNA solution obtained by the toothpick method. Although we tested PCR only with one primer set and one taq PCR kit, similar sensitivity as LAMP was not observed for the PCR method, thus corroborating previous reports that the LAMP method is superior to the PCR method in sensitivity (Kikuchi et al 2009;Nakao et al 2010;Thekisoe et al 2005;Tsai et al 2013).…”
Section: Discussionsupporting
confidence: 86%
“…5 b, c, d). Previous studies reported that sensitivity of LAMP was higher such as 10 times for the detection of fish pathogen [25], 20 times for the rapid detection of Avian Leucosis virus from culture isolates and clinical samples [26], 50 times for the detection of M. tuberculosis, M. avium, M. intracellulare for the diagnosis of pulmonary tuberculosis in microscopy Fig. 3 a- centre of developing countries [27,28] and 100 times more sensitive than conventional PCR [29] for the detection of yellow mosaic virus.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results of the LAMP assay can be interpreted using a simplified optical system or even with the naked eye. By taking advantage of this technology, the LAMP assay has been successfully applied to the diagnosis of some fish diseases [1,2,16,17,26]. The intergenic spacer region between the 16S-23S rRNA genes is an excellent candidate for the identification of bacterial species.…”
Section: Discussionmentioning
confidence: 99%